Parapharyngeal schwannoma—a challenging case report - Monteiro, Carlos (2020)
Parapharyngeal space primary neoplasias are infrequent findings in clinics, and schwannoma derived from a peripheral nerve is even rarer in this anatomic area [1]. The presented case is a patient who was referred to our department with a 3 months progressive soft palate enlargement without related symptoms. The challenge, in these cases, due to the anatomic complex area, is to catch a suitable approach to remove the tumor, according to dimension and surrounding structures. Prognosis and follow-up will depend on histopathologic evaluation.